Phytosynthesis of Eco-Friendly Silver Nanoparticles Using Lawsonia Innermis (L) and Their Biomedical Applications - Senthilkumaran Soowrish (Wolters Kluwer Medknow Publications, 2024)
BackgroundThe present study, plant extract to biosynthesize silver nanoparticles (AgNPs), is an environmentally benign way to lessen the use of dangerous chemicals. Aims and ObjectivesThe antibacterial effects of the green production of AgNPs by Lawsonia inermis extract were examined. Materials and MethodsUtilizing scanning, transmission electron microscopy, X-ray diffraction (XRD), ultraviolet-visible spectroscopy, and infrared spectroscopy, researchers examined the physical and chemical characteristics of synthesized AgNPs. ResultsAg-NPs have the highest peak in visible light at 460 nm, according to UV-vis analysis. When silver nanocrystals were structurally characterized, peaks that matched Bragg's diffractions were found, with average crystallite sizes ranging from 28 to 60 nm. Examining Ag-NPs' antibacterial properties, it was shown that all microbes are extremely sensitive to these biologically produced Ag-NPs. ConclusionEscherichia coli, Salmonella typhi, Bacillus cereus, and Staphylococcus aureus were tested for the antimicrobial properties of AgNPs synthesized.